2022
DOI: 10.1172/jci.insight.156950
|View full text |Cite
|
Sign up to set email alerts
|

A 4-week high-AGE diet does not impair glucose metabolism and vascular function in obese individuals

Abstract: Background: Accumulation of advanced glycation endproducts (AGEs) may contribute to the pathophysiology of type 2 diabetes and its vascular complications.AGEs are widely present in food, but whether restricting AGE intake improves risk factors for type 2 diabetes and vascular dysfunction is controversial. Research design and methods: Abdominally obese but otherwise healthy individuals were randomly assigned to a specifically designed 4-week diet low or high in AGEs in a double blind parallel-design. Insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…Stirban et al demonstrated that nutritional AGEs showed direct detrimental effects on the vasculature [ 109 ]. In contrast to Stirban et al’s result, Linkens et al could not find a correlation between high AGE levels and vascular complications [ 110 ].…”
Section: Pathogenesis Of Diabetic Vascular Complications and Ages In ...mentioning
confidence: 71%
“…Stirban et al demonstrated that nutritional AGEs showed direct detrimental effects on the vasculature [ 109 ]. In contrast to Stirban et al’s result, Linkens et al could not find a correlation between high AGE levels and vascular complications [ 110 ].…”
Section: Pathogenesis Of Diabetic Vascular Complications and Ages In ...mentioning
confidence: 71%
“…To date, the current literature has questioned many findings from animal and human studies due to the unreliability of the methods used for AGEs measurements. Most studies in the past predominantly measured AGE levels in foods using ELISA [ 61 , 62 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] instead of ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS), which is currently considered the gold standard for AGE measurements [ 19 , 104 ]. In addition, many studies focused on producing high-AGE and low-AGE diets using high and low baking (heat-treated) methods or changing the cooking technique (boiling, poaching instead of grilling, frying) to adjust the AGE concentrations in foods.…”
Section: Ages Oxidative Stress and Inflammation In The Gutmentioning
confidence: 99%
“…For example, studies in human participants with obesity revealed that one year of oral AGE restriction resulted in reduced insulin resistance compared to individuals consuming a regular AGE diet [14]. In contrast, a recent study reported that 4 weeks of consumption of a high-AGE diet in participants with obesity had no effect on glucose metabolism or vascular function [15]. The basis of these discrepancies may be due to such factors as the differences in the duration of AGE feeding, baseline adiposity, the metabolic state of the studies' participants, and the specific foods and their preparation modes deemed as "high" vs. "regular" or "low"-AGE.…”
Section: Advanced Glycation End-products (Ages)mentioning
confidence: 99%